FAKTOR YANG MENGHAMBAT PARTISIPASI MASYARAKAT PADA PROGRAM BANK SAMPAH DI KOTA YOGYAKARTA - Shafiera Amalia (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2020)
The waste bank program is implemented by the Yogyakarta City Environment Agency since 2012. However, the citizen participation to be the waste bank customer is low. The condition shows that people still do not have behavior and habit to manage the domestic waste. Therefore, it is necessary to find the reasons why public participation to become the waste bank customer is still low. This research used the qualitative approach and descriptive research type. The data collection techniques used were literature study; observation; and in-depth interviews. The data will be analyzed descriptively qualitatively. The results showed that only 18,855 heads of households (14.6%) out of 129,252 households in Yogyakarta City became the waste bank costumer. The sub-districts which have the largest proportion of waste bank customer with the number of households are Jetis and Mergangsan. Besides that, the sub-district which have the smallest proportion of the waste bank customer with the number of households is Gedongtengen. Three main obstructing factors cause the low public participation in the waste bank program in Yogyakarta City, namely: the knowledge of the waste management is not optimal; the lack of individual awareness and motivation to manage the waste; and less varied incentives